2019
DOI: 10.3390/su11051485
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Crop Management Strategies to Ensure Higher Crop Productivity within Sustainable Environments

Abstract: The rising population and reduction in the amount of land and some other resources have created tremendous pressure on current agricultural producers to meet the increasing food demands. To cope with this challenge, certain key inputs, such as fertilizers and other chemicals, are overused, which are worsening the surroundings. This intensive agricultural production without adherence to ecological sustainability has led to declining soil health, land degradation, and severe environmental problems. So, future ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
136
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 255 publications
(138 citation statements)
references
References 76 publications
1
136
0
1
Order By: Relevance
“…The net primary productivity of Phragmites in tropical wetlands has also been reported, ranging from 0.88 to 2.2 kg m −2 yr −1 [43,44]. Though data on net primary productivity of rice plants is not readily available due to great variations in soil and cropping management practices [45], an estimate by [46] showed that it's over six times less than that of macrophytes in natural wetlands. We obtained biomass densities in all sections of the natural section of the wetland in an order of magnitude greater than in the rice fields, supporting the high productivity of natural wetlands.…”
Section: Soil Organic Carbon In the Natural And Converted Sections Ofmentioning
confidence: 99%
“…The net primary productivity of Phragmites in tropical wetlands has also been reported, ranging from 0.88 to 2.2 kg m −2 yr −1 [43,44]. Though data on net primary productivity of rice plants is not readily available due to great variations in soil and cropping management practices [45], an estimate by [46] showed that it's over six times less than that of macrophytes in natural wetlands. We obtained biomass densities in all sections of the natural section of the wetland in an order of magnitude greater than in the rice fields, supporting the high productivity of natural wetlands.…”
Section: Soil Organic Carbon In the Natural And Converted Sections Ofmentioning
confidence: 99%
“…At this EC e, most of the crops are affected, while lower EC e s can also be unfavorable to certain crops [3,6]. Thus, strategies to develop tolerant varieties of plants to abiotic stresses are a major challenge so as to surpass the depleting food production system and meeting the global food demands [7].…”
Section: Introductionmentioning
confidence: 99%
“…Modern agriculture is faced with new challenges in the form of climate change and a growing global population, both of which has increased the demand for water usage. As water is one of the most important reserves for the sustainable development of agriculture, maximizing crop production per unit of water utilization has become a vital strategy to ensure future food security in dry semi‐humid regions (Shah & Wu, ; Wu & Ma, ). Increasing water‐use efficiency (WUE) through water‐saving technologies with efficient use of precipitation instead of relying on irrigation has gained extensive attention worldwide (Gan et al., ; Li et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ridges mulched with plastic film reduce heat exchange between the soil and ambient air, leading to increased topsoil temperature of mulched ridges and thus promoting seedling emergence and crop growth in winter wheat, except for a few studies reporting the negative effect of plastic film mulching in spring wheat (Li, Wang, & Xu, , , ). Additionally, the RFPFM system has several other advantages, such as reduced weeds and pests pressure, more efficient use of soil nutrients and solar radiation, better crop growth, and higher yield performance (Gan et al., ; Li et al., ; Shah & Wu, ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation